A leakage model of metallic static seals based on micromorphology characteristics of turning flange surface. Issue 6 (14th September 2015) - Liao, Chuanjun; Xu, Xibao; Fang, Hongrong; Wang, Hongrui; Man, Man
Abstract : Purpose: – The purpose of this paper is to develop a leakage model of metallic static seals, which can be used to accurately predict the leakage rate and study the corresponding seal characteristics. The metallic static seal is effectively applied to severe rugged environments where conventional seals cannot meet the needs. More research efforts for deepening the understanding of its seal characteristics are important for its effective and safe applications, of which the study about its leak is one key component. Design/methodology/approach: – In the microscopic observations of the turning surface that is general in the processing of flange surfaces, it is found that the spiral morphology is dominant, which had been also obtained by other researches. There are two potential leakage paths for the flange surface of spiral morphology, one is the radial direction perpendicular to the spiral ridges and the other is the circumferential direction along the spiral groove. Based on the microgeometry characteristics of spiral morphology, the micromorphology of turning flange surface is simplified for the calculation of leakage rate, and the simplified methods of the radial and circumferential leakage paths are presented separately. The topography of flange surface studied in this paper is actually measured, and the Abbott bearing surface curve is adopted to represent the micro-profiles parameters. The radial and circumferential leakage models are further developed based on the assumption of laminar flow of the viscous compressible gas. Findings: – The experiments used to verify the leakage models were carried out, and the experimental values are well agreed with the calculated values. As the contact pressure increases, the change rules of both radial and circumferential leakage rates are obtained and the obvious transition from radial leak to circumferential leak can be found. Using the proposed leakage models, the effects of the key micro-profiles parameters on the leakage rates are studied, and some specific conclusions are given simultaneously, which are favorable for the theoretical study and practical application of the metallic static seal. Practical implications: – By the interpretations of the micromorphology characteristics of turning flange surface, the leakage mechanism of the metallic static seal is further made clear. The proposed leakage model reveals the relationships between the key micro-profiles parameters and some sealing performances about the leakage and can predict the leakage rates of the metallic static seal used in various working conditions. Originality/value: – For the metallic static seal, the simplification of the radial leakage path and the radial leakage model are put forward for the first time, so the total leakage model can be systematically reported based on the micromorphology characteristics of turning flange surface. The effects of the key micro-profiles parameters on the seal behaviors including of the leak rate, critical contact pressure and transition from radial leak to circumferential leak etc are also clarified firstly.